K2-290: a warm Jupiter and a mini-Neptune in a triple-star system. Issue 3 (15th January 2019) - Hjorth, M; Justesen, A B; Hirano, T; Albrecht, S; Gandolfi, D; Dai, F; Alonso, R; Barragán, O; Esposito, M; Kuzuhara, M; Lam, K W F; Livingston, J H; et al.
ABSTRACT: We report the discovery of two transiting planets orbiting K2-290 (EPIC 249624646), a bright (V = 11.11) late F-type star residing in a triple-star system. It was observed during Campaign 15 of the K2 mission, and in order to confirm and characterize the system, follow-up spectroscopy and AO imaging were carried out using the FIES, HARPS, HARPS-N, and IRCS instruments. From AO imaging and Gaia data we identify two M-dwarf companions at a separation of 113 ± 2 and$2467_{-155}^{+177}$  au. From radial velocities, K2 photometry, and stellar characterization of the host star, we find the inner planet to be a mini-Neptune with a radius of 3.06 ± 0.16 R⊕ and an orbital period of P = 9.2 d. The radius of the mini-Neptune suggests that the planet is located above the radius valley, and with an incident flux of F ∼ 400 F⊕, it lies safely outside the super-Earth desert. The outer warm Jupiter has a mass of 0.774 ± 0.047 MJ and a radius of 1.006 ± 0.050 RJ, and orbits the host star every 48.4 d on an orbit with an eccentricity e < 0.241. Its mild eccentricity and mini-Neptune sibling suggest that the warm Jupiter originates from in situ formation or disc migration.